Modelling the distribution of Bonelli’s eagle in Spain: implications for conservation planning. - Muñoz-Gallego, Antonio Román; Real-Giménez, Raimundo; Barbosa, A. Márcia; Vargas-Yañez, Juan Mario (My University, 2005)
Bonelli’s eagle, Hieraaetus fasciatus , has recently suffered a severe population decline and is currently endangered. Spain supports about 70% of the European population. We used stepwise logistic regression on a set of environmental, spatial and human variables to model Bonelli’s eagle distribution in the 5167 UTM 10 × 10 km quadrats of peninsular Spain. We obtained a model based on 16 variables, which allowed us to identify favourable and unfavourable areas for this species in Spain, as well as intermediate favourability areas. We assessed the stepwise progression of the model by comparing the model’s predictions in each step with those of the final model, and selected a parsimonious explanatory model based on three variables — slope, July temperature and precipitation — comprising 76% of the predictive capacity of the final model. The reported presences in favourable and unfavourable areas suggest a source–sink dynamics in Bonelli’s eagle populations. The fragmented spatial structure of the favourable areas suggests the existence of a superimposed metapopulation dynamics. Previous LIFE (The Financial Instrument of the European Union for the Environment and Nature) projects for the conservation of this species have focused mainly on the northern limit of its range, where the sharpest population decline has been recorded. In these areas, favourability is low and Bonelli’s eagle populations are probably maintained by the immigration of juveniles produced in more favourable zones. However, southern populations, although stable, show signs of reduction in productivity, which could menace the population sizes in the whole study area. We suggest that conservation efforts should focus also on known favourable areas, which might favour population persistence in unfavourable areas through dispersal.
OA
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/6798?template=romeo
Keywords: Especies protegidas; Espacios naturales protegidos - Modelos matemáticos; Endangered species; Favourable areas; LIFE projects; Metapopulation; Predictive models; Explanatory models; Source–sink dynamics